2016
DOI: 10.1097/nmd.0000000000000537
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Self-stigma Between People With Different Mental Disorders in Taiwan

Abstract: Internalized stigma (or self-stigma), one of the most painful effects of stigma, causes people with mental health problems profound negative consequences, for example, psychological adversity, demoralization, and feelings of hopelessness. However, knowledge about self-stigma in people with different mental disorders is insufficient. We hypothesized that people with different psychiatric diagnoses have different levels of self-stigma. Through convenience sampling, we used the Internalized Stigma of Mental Illne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(56 citation statements)
references
References 43 publications
(53 reference statements)
5
51
0
Order By: Relevance
“…Higher insight into illness significantly predicted the level of self-stigma, in accordance with several studies [11,66]. A history of suicide attempt was associated with elevated self-stigma as found in other studies [67,68]. As self-stigma moderates the relationship between insight into illness and depression, it can be supposed that recoveryoriented interventions targeting self-stigma reduction could protect against depression and suicidal ideation and should be further developed [13,14].…”
Section: European Psychiatrysupporting
confidence: 87%
“…Higher insight into illness significantly predicted the level of self-stigma, in accordance with several studies [11,66]. A history of suicide attempt was associated with elevated self-stigma as found in other studies [67,68]. As self-stigma moderates the relationship between insight into illness and depression, it can be supposed that recoveryoriented interventions targeting self-stigma reduction could protect against depression and suicidal ideation and should be further developed [13,14].…”
Section: European Psychiatrysupporting
confidence: 87%
“…In our interviews, one female participant reported she was often a target of both verbal and emotional abuse from her mother who often accused her of being lazy and useless and that she (her mother) wished she was dead. This emotional abandonment and abuse by family members aligns with results from other studies [70,71], and has particular implications for health service providers who may be unaware of the nature and dynamics of familial relations.…”
Section: Stigma and Discrimination Compounded By Socio-cultural Beliefssupporting
confidence: 79%
“…Affiliate stigma associated with Alzheimer's disease has three key components: cognitive attributions (neglectful caregiver and punishment from God), emotional reactions (anger, fear and shame) and behavioral reactions (concealment, isolation, and not seeking help) [13]. This internalization may lead to serious consequences, such as lower self-esteem and self-efficacy, feelings of hopelessness, and poor quality of life according to the stigma studies with family caregivers of people with mental illness [14][15][16][17]. Studies have indicated that family caregivers who perceive stigmatization experience high stress, negative emotions, a high care burden, and social isolation; they engage in less help-seeking behaviors and may be unable to provide high-quality care [18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%